MECHANISM OF SUPPORTING THE ECONOMIC BALANCE IN THE SPHERE OF HOUSING AND COMMUNAL SERVICES - Bekirova, Olga; Trifonova, Maria; Stroganova, Yana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Housing and communal services is one of the leading branches of the municipal economy at the present time, the quality of life of the population directly depends on the effectiveness of its development. Despite the high level of development of many socio-economic entities in the Russian Federation, in the housing and public utilities sector today there is no uniform effective methodology for assessing ongoing activities. Creating a universal methodology for assessing regional authorities in the implementation of measures to reform housing and communal services can be an important element in the information management of the industry. The scientific paper uses mathematical tools to build effective mechanisms for the functioning of programmes for housing and public utilities.The purpose of this study is a theoretical justification, the creation of an effective mechanism to maintain the economic balance in the housing sector.In this case, effective monitoring of management companies is considered as an important element of the economic mechanism of management of housing and public utilities, which will improve the quality of public services and ensure the level of satisfaction of the population.